2016
DOI: 10.1039/c5ce02134k
|View full text |Cite
|
Sign up to set email alerts
|

Ambient synthesis of a multifunctional 1D/2D hierarchical Ag–Ag2S nanowire/nanosheet heterostructure with diverse applications

Abstract: Dou, S. (2016). Ambient synthesis of a multifunctional 1D/2D hierarchical Ag-Ag2S nanowire/nanosheet heterostructure with diverse applications. CrystEngComm, 18 (6), 930-937. Ambient synthesis of a multifunctional 1D/2D hierarchical Ag-Ag2S nanowire/nanosheet heterostructure with diverse applications AbstractA new type of unique 1D/2D hierarchical Ag-Ag2S heterostructures is fabricated by an extremely simple solution route under ambient conditions. The morphology, size, crystal structure and composition of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(21 citation statements)
references
References 59 publications
0
21
0
Order By: Relevance
“…In the current work, Ag nanocubes with spatially different reactivity were applied as templates, which eventually resulted in gradually varying shell thickness in the synthesized Ag@Ag 2 S core@shell structures. Previously, Ag-Ag 2 S hybrids of different shapes including nanowires 24 , nanocubes 15 , 25 , triangular nanoplates 15 , and nanoprisms 26 , 27 were synthesized via the sulfudition of the corresponding Ag nanocrystals. In those studies, the resulting hybrids possessed the same shapes as the Ag nanocrystals.…”
Section: Introductionmentioning
confidence: 99%
“…In the current work, Ag nanocubes with spatially different reactivity were applied as templates, which eventually resulted in gradually varying shell thickness in the synthesized Ag@Ag 2 S core@shell structures. Previously, Ag-Ag 2 S hybrids of different shapes including nanowires 24 , nanocubes 15 , 25 , triangular nanoplates 15 , and nanoprisms 26 , 27 were synthesized via the sulfudition of the corresponding Ag nanocrystals. In those studies, the resulting hybrids possessed the same shapes as the Ag nanocrystals.…”
Section: Introductionmentioning
confidence: 99%
“…43 The spectral results observed herein could possibly reflect contributions to the synergistic effects between the Ag NWs and CdS shell in the Ag@CdS hybrids and provide strong evidence that the Ag NWs have essentially turned into Ag@CdS hybrids, with the product mainly composed of the CdS component, 44 as well as suggesting that the good contact between the Ag core and CdS shell might ensure effective charge transfer across the phase boundary and cause changes in the structure and shape of the product. 45,46 Their broad absorbance from the UV to the near-infrared window is crucial for the full use of sunlight. Interestingly, it was found that the addition of ammonia, Cd(NO 3 ) 2 ·4H 2 O, and thiourea play important roles in the construction of such 1D hierarchical nanostructures assembled from nanosheets and nanoparticles on nanowires.…”
Section: Resultsmentioning
confidence: 99%
“…[1] In particular, as one of the most important JNPs, the noble metal-semiconductor composite systems have been investigated widely due to their well-known remarkable optical, electrical, magnetic and catalytic properties, [2] Considerable efforts have been devoted to synthesize noble metal-semiconductor composite, for instance, Au-ZnO, [3] Au-Ag2S, [4] and Ag-Ag2S. [5], Among these noble metal-semiconductors, Ag-Ag2S nanohybrids were reported with excellent properties in resistive switches, [6] photodegradation of pollutants, [7] and water splitting [8]. Owing to its excellent photoelectric and photocatalytic properties, it is still necessary to explore a facile and rational synthetic strategy to synthesize Janus Ag-Ag2S heterostructures and investigate their novel properties and potential applications.…”
Section: Introductionmentioning
confidence: 99%